1976
DOI: 10.1017/s0021900200103985
|View full text |Cite
|
Sign up to set email alerts
|

On a stochastic differential equation modeling of prey-predator evolution

Abstract: We study a stochastic differential equation model of prey-predator evolution. To keep in line with a known deterministic model we include the social and interaction terms with the drift in our model, and the randomness arises as fluctuations in the ecosystem. The notion of equilibrium population level and special types of fluctuations force us to work with degenerate elliptic operators. We consider the propagation of the population system in a sufficiently large but bounded domain. This enables us to look at n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Gard and Kannan [6] studied the classical prey-predator model with the rates perturbed by Gaussian white noise. They studied (3) in the case that γ < 0 and δ < 0, and showed that, on the set of realizations where it remains bounded for all time, the solution converges to the fixed point (x * , y * ) [6, Theorem 3.1] or converges to the boundary of the bounding set [6, Theorem 3.2].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Gard and Kannan [6] studied the classical prey-predator model with the rates perturbed by Gaussian white noise. They studied (3) in the case that γ < 0 and δ < 0, and showed that, on the set of realizations where it remains bounded for all time, the solution converges to the fixed point (x * , y * ) [6, Theorem 3.1] or converges to the boundary of the bounding set [6, Theorem 3.2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recall the definition of F in (6). From (7), we have Stochastic competing species and ergodicity 747 and, therefore,…”
Section: Then Lim X→∞ H (X) < ∞mentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, the error process is considered as mainly measurement (observation) error, which does not interfere with the deterministic function. In practice, this assumption is related to the fact that, had this interference been present, the oscillatory behaviour might have been lost, as is the case in the corresponding Lotka-Volterra stochastic differential equations (SDEs) models (see, e.g., [7][8][9]). …”
Section: S Nkurunzizamentioning
confidence: 99%
“…Tsokos and Hinkley (1973) studied the behaviour of the system by formulating a general bivariate stochastic model and derived estimators for its parameters. Gard and Kannan (1976) developed a stochastic differential equation model of prey-predator evolution and studied population extinction. Billard (1977) considered the case in which interactions of two species occur over a sufficiently short period of time during which no births occur, and provided complete solutions for this stochastic model.…”
Section: Introductionmentioning
confidence: 99%